Income Diversification Through Optimization of Service Rates at Universi-tas Negeri Semarang - Kurniasih, Fransiska Novi; Widayanti, Wiwik; Wicaksana, Tania (Future Science / FSH-PH Publications, 2023)
Improving the quality of education is a complex matter because it is related to technical problems and the planning, administration, funding, management of income sources, diversification of service rates, and effectiveness and efficiency of the education system. Semarang State University (Unnes) is one of the universities still categorized as a Public Service Agency, which is still transforming into a legal entity university (PTNBH). This study aims to determine the income from the current service tariffs, map the potential for additional revenue from available services, and analyze revenue potential by simulating new service tariffs. The method used in this research is qualitative descriptive. The study results show that the management and transparency of easily obtained university budgeting guide data will reduce the risk of budget management. Budget diversification will minimize the risk so that budget management will run more effectively and efficiently. Furthermore, it is known that the service tariffs that have been in effect so far are considered not optimal and can still be developed into the potential for diversifying the Institution's income. That makes it possible to enter work contracts with external parties to optimize revenue potential and better quality management.